Intercultural Dialogue and Tolerance in the Globalizing World - Aliyeva, Sahiba (Scholarya Demo Journal of Ruby, 2019)
The article highlights the importance of intercultural dialogue, one of themost global issues of the modern era, that unites nations of the world,combining national and universal characteristics. Theoretical and practical aspects of intercultural dialogue are explored as well. Promoting values ofmulticulturalism, Azerbaijan demonstrates a culture that will exemplify theworld's nations. The article propagates Azerbaijan's model of multiculturalism.On the one hand, rallies concerning racism in Europe, racial discrimination andnational unity, increasing Islamophobia in Western countries, West-EastConflict, crisis of multicultural values in Western countries which joinedUnited Nations Charter, OSCE Decisions and Recommendations andInternational Conventions, migration crisis, critical situation that migrants face,migration to Europe in the wake of large-scale wars in the East, the attitude ofthe Eastern countries to the migration, the attitude towards the Azerbaijanis,important issues such as the organization of state-level events for the survivaland activity of small nations are reflected in the article.The article deals with national-ethnic processes, ethnogenesis problem,social dynamics of the development of national minorities and minorities livingin different states, the reforms carried out by independent Azerbaijan based onthe world-wide political and legal agreements, conventions, acts andcommitments in regards to these processes and their practical results werereflected. After the independence, the most important issue of the statehood inAzerbaijan was ideology of “Azerbaijanism” formed by National LeaderHeydar Aliyev, and the interpretation of the provisions concerning theprotection of the rights and freedoms of ethnic minorities, which is part of thisideology was discussed in the article. It also discusses the example of theAzerbaijani state, which demonstrated great multicultural values, the essenceof the “Baku Process”, the establishment of Baku InternationalMulticulturalism Center as a model of tolerance for the world, the organizationof intercultural and interreligious dialogue and their international significance.